Assistance for intellectual disability teenager to prevent sexual harassment with educational films at SLB N Semarang - Aprianti Aprianti; Fitria Dewi Puspita Anggraini; Kismi Mubarokah; Meryna Puspita Dewi (Community Empowerment, 2022)
Adolescents with intellectual disability who do not have intelligence abilities are vulnerable to sexual harassment when their reproductive systems are developing. Consequently, they lack a comprehensive understanding of reproductive health. This service aims to provide assistance to 38 intellectual disability teenagers at SLB N Semarang. Assistance is carried out through the stages of strengthening cooperation, pre-test, film screening, brainstorming, and post-test. The outcomes revealed that there was an increase in knowledge after the intervention, which took the form of showing a short film about pregnancy prevention (p-value 0.009), with low program effectiveness (gain score 0.29).